Oxygen mass transfer in fermentation of bacillus thuringiensis (1999)
The purpose of this work was to obtain a correlation based on literature, depicting the relationships betwen the physical oxygen transfer rate (OTR) and microbial oxygen uptake rate (OUR) in order to determine the conditions (mass transfer coefficient, resulting on diferents combinations of aereations and agitations rates), under which growth will not be limited by oxygen. This correlation was adapted to culture with B. thuringiensis in order to estimate what biomass concentration are feasible for the physical limits set by operations conditions before microbial activity becomes limited by oxygen.